The tradeoff between relevance and comparability in segment reporting. Issue 1 (December 2019) - Hinson, Lisa; Tucker, Jennifer Wu; Weng, Diana
Abstract: The rule change for segment reporting in 1998 has arguably made segment reporting more relevant through the adoption of the management approach. Meanwhile, the management approach has resulted in a decrease in the comparability of segment income. We introduce firm-specific measures of changes in relevance and comparability due to the rule change. Our treatment firms experienced an increase in the relevance of segment reporting but a large decrease in the comparability of segment income; our benchmark firms barely experienced any changes in relevance and comparability. We examine earnings forecasts before vs. after the rule change issued by financial analysts—a major user group of segment reporting. Relative to benchmark firms, treatment firms' analyst forecast error reductions around the segment disclosure event are not significantly different after the rule change than before the rule change, but treatment firms' forecast dispersion reductions around the segment disclosure event are significantly larger after the rule change than before the rule change. These results suggest that despite the decrease in comparability, the new segment reporting rule has increased the decision usefulness of segment information by decreasing disagreement among analysts.